2015
DOI: 10.1016/j.celrep.2015.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protection by Exogenous Otx2 in Mouse Retinal Neurons

Abstract: Mutations of orthodentricle homeobox 2 (OTX2) in human and mice often cause retinal dystrophy and nyctalopia, suggesting a role of OTX2 in mature retina, in addition to its functions in the development of the eye and retina. In support of this, the number of bipolar cells in Otx2 +/− post-natal mouse retina was found to be significantly lower than normal. Degeneration of the cells becomes greater as the mice age, leading to the loss of vision. Especially, the type-2 OFF-cone bipolar cells, which do not express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…PNNs specifically capture and transfer othodenticle homeobox 2 (Otx2), an essential protein for the maturation of PV(+) interneurons 48 into the cells 49 . It has been reported that Otx2 has a neuroprotective effect by restoring mitochondrial dysfunction in mice retinas 50 . Furthermore, PNNs are found to protect PV(+) interneurons against oxidative stress in rodent prefrontal cortex 51 .…”
Section: Discussionmentioning
confidence: 99%
“…PNNs specifically capture and transfer othodenticle homeobox 2 (Otx2), an essential protein for the maturation of PV(+) interneurons 48 into the cells 49 . It has been reported that Otx2 has a neuroprotective effect by restoring mitochondrial dysfunction in mice retinas 50 . Furthermore, PNNs are found to protect PV(+) interneurons against oxidative stress in rodent prefrontal cortex 51 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, severe sensorineural deafness could be considered a typical manifestation of complex phenotypic spectrum caused by major mitochondrial dysfunction. Despite some experimental evidences emphasize the potential role of exogenous OTX2 in mitochondrial respiratory chain function and regulation (Kim et al, ), severe cerebellar atrophy together with myopathy and multiple mitochondrial respiratory chain defects, do not appear to be immediately correlated to OTX2 mutation and/or biological function.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, OTX2 protein is restricted to the neurons of the central and medial-ventral VTA of the ventral midbrain (Di Salvio et al, 2010a, 2010b), and could protect VTA DA neurons against MPTP-induced neurodegeneration by down-regulating the expression of Girk2 and DAT (Di Salvio et al, 2010a, 2010b) and up-regulating the expression of neuropeptides (Chung et al, 2010). Furthermore, in retinal bipolar cells, OTX2 was reported to resist glutamate excitotoxicity (Kim et al, 2015). These results indicate that OTX2 might be an effective protective factor for neurons against the toxic effect of MPTP or other toxins, and could be used as a therapeutic target in Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%